2007
DOI: 10.1002/ccd.21246
|View full text |Cite
|
Sign up to set email alerts
|

Drug eluting stents versus coronary artery bypass surgery in patients with isolated proximal lesion in left anterior descending artery suffering from chronic stable angina

Abstract: The present study demonstrated that patients suffering from chronic stable angina with isolated lesion in the proximal segment of LAD have excellent long-term outcome in both surgical and DES treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…Other studies described similar relief of angina in the range of 67% to 96% for PCI and 83% to 85% for MIDCAB (7,22,23). For PCI in general, several studies …”
Section: Discussionmentioning
confidence: 84%
“…Other studies described similar relief of angina in the range of 67% to 96% for PCI and 83% to 85% for MIDCAB (7,22,23). For PCI in general, several studies …”
Section: Discussionmentioning
confidence: 84%
“…Several published studies demonstrated that late patency of the internal mammary artery grafts was superior to DES when it comes to treating the proximal lesion in LAD. 45,46 In addition, each patient treated with CABG in our study has a LIMA to LAD graft. The factors mentioned above principally account for the lower rate of repeat revascularization in the CABG group.…”
Section: Discussionmentioning
confidence: 99%
“…Our search yielded 332 relevant reports, and after screening and reviewing full manuscripts, 12 studies met the inclusion criteria (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The process of study selection is shown in Figure 1.…”
Section: Quantity Of Evidencementioning
confidence: 99%
“…The study designs and participant characteristics of the included studies are listed in Tables 1,2. There were three randomized controlled trials (RCTs) (11,18,21) and nine cohort studies (10,(12)(13)(14)(15)(16)(17)19,20). Most studies had >100 participants in each arm except for four studies (11,14,18,21).…”
Section: Quality Of Evidencementioning
confidence: 99%